The pragmatic Whitman : reimagining American democracy - Mack, Stephen John, 1952- (Iowa Whitman series., 2002)
In this surprisingly timely book, Stephen Mack examines Whitman's particular and fascinating brand of patriotism: his far-reaching vision of democracy. For Whitman, loyalty to America was loyalty to democracy. Since the idea that democracy is not just a political process but a social and cultural process as well is associated with American pragmatism, Mack relies on the pragmatic tradition of Emerson, James, Dewey, Mead, and Rorty to demonstrate the ways in which Whitman resides in this tradition. Mack analyzes Whitman's democratic vision both in its parts and as a whole; he also describ.